Evaluation of a diagnostic algorithm for rapid identification of Gram-negative species and detection of extended-spectrum β-lactamase and carbapenemase directly from blood cultures. (19th July 2022) - Comini, Sara; Bianco, Gabriele; Boattini, Matteo; Banche, Giuliana; Ricciardelli, Guido; Allizond, Valeria; Cavallo, Rossana; Costa, Cristina
Abstract: Objectives: To evaluate a rapid diagnostic algorithm based on MALDI-TOF MS, lateral flow immunoassays (LFIAs) and molecular testing performed directly from positive blood cultures (BCs) for Gram-negative species identification and detection of CTX-M extended-spectrum β-lactamases and main carbapenemases. Methods: Non-duplicate BCs positive to Gram-negative bacteria at microscope examination were subjected to species identification by direct MALDI-TOF MS following recovery of bacterial pellet by Rapid MBT Sepsityper ® kit. Subsequently, NG-Test ® CARBA 5 and NG-Test ® CTX-M MULTI LFIAs were performed according to identified microbial species. Eazyplex ® SuperBug CRE molecular assay was performed in cases of NG-Test ® CARBA 5 negative results in patients with documented carbapenemase-producers carriage. Results of rapid diagnostic workflow were compared with those obtained by conventional diagnostic routine. Results: Overall, the direct MALDI-TOF MS protocol allowed reliable identification to the species level of 92.1% of the 2133 monomicrobial BCs. Rate of matched identification was significantly higher for Enterobacterales (97.3%) in comparison to non-fermenting Gram-negative species (80.2%), obligate anaerobic bacteria (42.1%) and fastidious Gram-negative species (41.5%). The overall sensitivity of NG-Test ® CARBA 5 and NG-Test ® CTX-M MULTI was 92.2% and 91.6%, respectively. Integration of Easyplex ® SuperBug CRE allowed the detection of bla KPC mutants associated with ceftazidime/avibactam resistance, reaching 100% sensitivity in carbapenemase detection. Both LFIAs and molecular testing showed no false-positive results. Conclusions: Algorithms based on MALDI-TOF MS, LFIAs and molecular testing may represent a cost-effective tool to timely identify Gram-negative species and detect resistance markers directly from BCs. According to local epidemiology, these results may allow antimicrobial stewardship interventions including prompt use of new approved drugs.